2011
DOI: 10.1182/blood-2010-08-303115
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor death-associated protein kinase is required for full IL-1β production

Abstract: Interleukin-1␤ (IL-1␤ IntroductionInterleukin-1␤ (IL-1␤) plays an important role in infection and inflammation. 1 The generation of IL-1␤ is divided into 2 stages. In the first stage, inflammatory stimuli activate nuclear factor-B (NF-B) to promote the synthesis of pro-IL-1␤. In the second stage, pro-IL-1␤ protein is cleaved by caspase-1 to generate mature p17 IL-1␤ protein. The activation of caspase-1 is dependent on the formation of large multiprotein complexes inflammasomes in macrophages and monocytes. [2]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 50 publications
2
53
2
Order By: Relevance
“…It was reported that knockdown of DAPK1 attenuated interleukin 1β production in macrophages. 16 On the other hand, it was shown that DAPK1 and DAPK3 had negative regulatory roles in the expression of inflammatory genes, including ribosomal protein L13a, extracellular signal-regulated kinase, and interferon-γ-activated inhibitor of translation in macrophages.…”
Section: October 2012mentioning
confidence: 99%
“…It was reported that knockdown of DAPK1 attenuated interleukin 1β production in macrophages. 16 On the other hand, it was shown that DAPK1 and DAPK3 had negative regulatory roles in the expression of inflammatory genes, including ribosomal protein L13a, extracellular signal-regulated kinase, and interferon-γ-activated inhibitor of translation in macrophages.…”
Section: October 2012mentioning
confidence: 99%
“…To test this hypothesis, two sets of experiments were performed. First, we examined the effect of the V protein on IL-1␤ secretion of HEK293T cells transiently transfected with plasmids encoding components of the NLRP3 inflammasome: NLRP3, ASC, procaspase-1, and pro-IL-1␤ (10). In this experiment, HEK293T cells were used, as they are human cells that can be transfected at a high efficiency.…”
Section: V Protein Inhibits Mv-induced Il-1␤ Secretionmentioning
confidence: 99%
“…3), we examined whether TIFA phosphorylation and oligomerization can induce the assembly and activation of NLRP3 inflammasome. To functionally link Akt phosphorylation of TIFA with inflammasome activation, we performed an NLRP3 inflammasome reconstitution assay in HEK293T cells lacking the endogenous inflammasome core proteins (23,24). HEK293T cells were cotransfected with NLRP3, ASC, procaspase-1, and pro-IL-1β together with Akt WT, TIFA siRNA, Akt K14R (i.e., loss-of-function mutant), or Akt E17K (i.e., gain-of-function mutant).…”
Section: Tifa Induces the Assembly And Activation Of Nlrp3 Inflammasomentioning
confidence: 99%